PENGARUH PROGRAM DIRECT MARKETING TERHADAP KEPUTUSAN MENGGUNAKAN MEETING PACKAGE GRAND HOTEL LEMBANG (Survei pada Tamu Bisnis di Grand Hotel Lembang) - Hendria, Repiyanti; Ahman, Eeng; Novalita, Dewi Pancawati (THE Journal : Tourism and Hospitality Essentials Journal, 2014)
Service industry is a collection of various company that centralise their service effort to their consumer. Sort efforts that included to this categoryare hotel, resort, restaurant, coffee shop, bar, pub and other. Tourism developing become an industry then the tourism service marketing, include the hotel industry, will be more important. At the moment, world tourism’s trend is directed to Meeting, Incentive, Conference and Exhibition (MICE) industry. MICE is a kind of business that give high contribution on economies especially for hotel industry. Grand Hotel Lembang, as one of the oldest and the biggest hotel in Lembang, also participate to complete tourist’s need especially for them as business guest to have a meeting activity. Various effort have done to attract tourist’s interest to visit this hotel. One of the efforts is direct marketing program which consist of direct mail, telemarketing, and face to face selling directed to business tourist as analyst unit in this research. Based on the available secondary data, there is the phenomenon of a decrease in the number of Grand Hotel Lembang meeting package of business guest.Verificative descriptive and explanatory method of survey used in this reserch. The sample of this research are 63 people by using stratified random sampling approach in cross-sectional method, while for the data analysis techniques used in this study is simple linier regression. This research used independent variable namely direct marketing (X) and dependent variable namely decision to use meeting package (Y). The result showed that significant influence exist from direct marketing program toward the decision to use Grand Hotel Lembang meeting package with telemarketing as the most influential indicator. Meanwhile the lowest indicator is direct mail. This showed that Grand Hotel Lembang has to increase the direct mail performance especially hotel publicity to be more widely recognized by the business guest. Management performance or promotion program implemented by Grand Hotel Lembang need to be improved so that more and more business guest use Grand Hotel Lembang meeting package for increasing hotel revenue.